The Extent of Inclusion of Future Forecasts Requirements in the intermediate first-grade Science Course in Saudi Arabia - Almaghrabi, Bushra Habib; Subhi, Nisreen Hassan (Journal of Educational and Psychological Sciences, 2021)
The study to identify the extent to which the requirements for future development are included in the science courses for the intermediate first-grade in the Kingdome of Saudi Arabia, To achieve the objectives of the study we used the descriptive-analytical approach, The tool was represented in the list of an analysis of the content of science courses for the intermediate first-grade in Saudi Arabia in light of the six axes of the specific future-forward requirements (Natural outlook, environmental outlook, food outlook, healthy outlook, community outlook, economic outlook), It includes (43) sub-requirements, applied to the sample of science courses for the first grade, in the first and second semesters of 1441-2019, The results of the study showed that the inclusion of the requirement for environmental foresight in the content of science courses for the first middle grade of science courses was (46%) Which is a moderate ratio, Followed by natural outlook with a guaranteed percentage (41%), followed by food and health outlook swelled to the same rate as (3.8%). Which is a low percentage, Then the community outlook and economic outlook came with the lowest percentages of (2.5%), also it was concluded that there are some forward-looking requirements not included in the content of science courses for the intermediate first-grade They are: genetically modified foods, preservatives additives, artificial colors, hormone therapy, laser therapy, alternative medicine, gene therapy, misuse of vitamins and steroids, traffic congestion, industry, In light of the results, several recommendations and proposals were made for the development of science curricula in light of the requirements for future development. The most important ones are attention to the main and sub-future requirements reached by the study by those responsible for the development and preparation of the curricula of intermediate first-grade sciences. And Increased attention to key and sub-future requirements that were received in small proportions in the content of intermediate first-grade science courses.
Keywords: Future Forecasts Requirements; Science Course; intermediate first-grade